Obrazy. 5 (Gli altri e) Ruben Nikolaevič Simonov: buio e resto del giorno. II: Profili di registi della seconda generazione russa - Lenzi, Massimo (Mimesis Journal, 2015)
Fourth and final part of the profile dedicated to Ruben Nikolayevich Simonov (1899-1968), which reconstructs the final period of his leadership of the Vakhtangov Theater in Moscow, to which he entirely dedicated his artistic life. The essay explains his activities as a director and actor in the fifties and sixties intertwined with that of other leading directors of the theater, in particular his son Yevgeny and Aleksandra Remizova.